2016
DOI: 10.1108/srj-05-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Differential reporting of social and environmental disclosures between local and foreign oil companies in Nigeria

Abstract: Purpose This study aims to identify the differences between local and foreign companies’ social and environmental disclosures (SEDs) practices operating in the Nigerian oil sector. It aims at distinguishing SED levels by comparing local and foreign companies operating in the oil sector. Design/methodology/approach The paper analyses annual reports through content analysis. SED extent and type are measured by the number of sentences. SEDs are further classified into three subcategories according to whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Similarly, previous empirical studies Deegan and Gordon (1996), Hackston and Milne (1996), Deegan and Rankin (1996), Harte and Owen (1991), Cho et al (2010), andOdera et al (2016) found that companies used CSER as a tool to improve their company image by selectively disclosing positive social and/or environmental information and little or no negative information. In this study, some participants also revealed that their companies never disclosed negative information in their CSR reports.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, previous empirical studies Deegan and Gordon (1996), Hackston and Milne (1996), Deegan and Rankin (1996), Harte and Owen (1991), Cho et al (2010), andOdera et al (2016) found that companies used CSER as a tool to improve their company image by selectively disclosing positive social and/or environmental information and little or no negative information. In this study, some participants also revealed that their companies never disclosed negative information in their CSR reports.…”
Section: Discussionsupporting
confidence: 57%
“…Content analysis refers to the process of making inferences based on objective coding of information. One of the major strengths of this type of analysis is its generalizability given that it uses voluminous numerical data to establish significant relationships (Odera et al , 2016). Annual reports were chosen to measure CSRR since they are formal public documents produced by companies and are the most accessible source of information for listed companies.…”
Section: Methodsmentioning
confidence: 99%
“…Abdo & Aldrugi (2012) state that differences in the nature of the CSRR depends on the company's country of ultimate ownership. Alternatively, it could be argued that the very nature of internationalisation, by companies of any nationality, leads to an increase in CSRR (Odera et al, 2016). Country context and type of industry have an impact on their reports in terms of their CSRR styles (Islam et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations